Exploring maternal parenting practices and their role in toddler stunting: a case study in North Jakarta - Nabila Akmal, Zahra; Anggraini, Suci; Feriningsih, Wida; Rahayu, Sri (Jurnal Kesehatan Ibu dan Anak, 2025)
Stunting remains a significant public health issue in Indonesia, particularly in urban areas such as North Jakarta. Maternal parenting practices encompassing feeding, hygiene, and healthcare behaviors are recognized as key contributors to child nutritional outcomes. However, in specific communities like Posyandu RW 010, where five stunted toddlers have been identified, the underlying parenting dynamics remain poorly understood.  This study aims to explore maternal parenting practices including feeding, hygiene, and healthcare utilization among mothers of stunted toddlers in RW 010 Posyandu, North Jakarta, to identify underlying contributing factors to persistent stunting cases. This qualitative study employed a case study approach to explore maternal parenting practices among mothers of stunted toddlers in RW 010, Tugu Utara Village, North Jakarta, Indonesia. Data were collected in December 2024 through in-depth interviews, non-participant observations, and document reviews. Participants included three mothers of stunted children, one Posyandu cadre, and one local community leader, selected through purposive sampling based on inclusion criteria such as low education level, stunted child status, and willingness to participate. Data were analyzed thematically using data reduction, display, and conclusion drawing. Triangulation was applied across data sources, collection techniques, and informants to enhance credibility. The findings revealed suboptimal parenting practices, including incomplete exclusive breastfeeding, unbalanced and monotonous complementary feeding, poor hygiene behaviors (e.g., handwashing without soap), and inconsistent utilization of health services, with some children missing immunizations. Despite the involvement of health services and the support of husbands, limited assistance from extended family and gaps in maternal knowledge were noted. Socioeconomic constraints and cultural beliefs also influenced caregiving practices. This study underscores the complex interplay of maternal behavior, household environment, and social support in the persistence of stunting. The qualitative approach enabled an in-depth understanding of local parenting dynamics that may not be captured through quantitative surveys. Strengthening health education, particularly tailored to local contexts, and expanding family and community engagement are critical to improving stunting prevention efforts.